Systematic study of proton-induced spallation reactions with microscopic and phenomenological models - Assimakopoulou, A.; Souliotis, G. A.; Nicolis, N.; Veselsky, M.; Bonasera, A. (HNPS Advances in Nuclear Physics, 2019)
Proton induced spallation reactions on 238U, 208Pb, 181Ta and 197Au targets at high energies were investigated using the microscopic Contrained Molecular Dynamics (CoMD) model and the phenomenological models INC and SMM. We have calculated the total fission cross sections, the ratio fission cross section to residue cross section, the mass yield curves and the excitation energy after the intranuclear cascade using the CoMD model and the INC/SMM phenomenological models. We made a comparison between the models and the experimental data from the liter- ature. Our calculations showed satisfactory agreement with available experimental data and suggest further improvements in the models. Our study with the CoMD code represents the first complete dynamical description of the spallation process with a microscopic code based on an effective nucleon-nucleon interaction.